Music and its meaning, how has the last 30 years of music psychology research progressed our knowledge? - Sloboda, John Anthony (Interdisciplinary Studies in Musicology, 2018)
There are three different types of scholarship, primary, secondary, and meta-scholarship. This paper applies a meta-approach to the question of musical meaning, which involves some assessment of where the enterprise as a whole has come from and is heading, its value and external impact. Three aspects of meaning are discussed: referential, functional and socially transformative. Referential meaning refers to our ability to apprehend a musical object as pointing beyond itself. Functional meaning refers to valued personal outcomes that musical engagement engenders. Transformative meaning refers to effects on the wider society. Consultative data from an expert panel is used to frame the discussion. This data shows multiple ways in which recent psychology research has advanced our understanding of how music acquires referential and functional meaning. To date, stronger theoretical clarity has been achieved in the area of referential meaning than in functional meaning. The strongest socially transformative effect of music psychology research has been on the discipline of musicology itself. Weaker, but still significant, effects are found in the wider society, relating to understandings of the benefits of musical engagement, and the acceptance universality of musical capacity as an inherent human attribute.